Investigation of 3D-Printed Polycaprolactone-/Polyvinylpyrrolidone-Based Constructs - Izgordu, Muhammet Sefa; Uzgur, Evren Isa; Ulag, Songul; Sahin, Ali; Yilmaz, Betul Karademir; Kilic, Beyhan; Ekren, Nazmi; Oktar, Faik Nuzhet; Gunduz, Oguzhan (SAGE PUBLICATIONS INC, 2021)
The aim of this study is to evaluate the mechanical and biological performance of cartilage-like constructs produced by 3D printing. During the investigation, poly(epsilon-caprolactone) (PCL) and polyvinylpyrrolidone (PVP) were used as a matrix polymer and low-molecular-weight chitosan (CS), hyaluronic acid (HA), and alginic acid sodium salt (SA) were integrated separately with the polymer matrix to fabricate the constructs. Thermal, mechanical, morphology, and chemical properties and swelling, degradation, and biocompatibility behaviors were evaluated in detail. With the addition of 3 fillers, the melting temperature of the matrix increased with the addition of fillers, and PCL/3wt.%PVP/1wt.%HA had the highest melting temperature value. Mechanical characterization results demonstrated that the printed PCL/3wt.%PVP/1wt.%CS displayed the highest compressive strength of around 9.51 MPa. The compressive strength difference between the PCL/3wt.%PVP and PCL/3wt.%PVP/1wt.%CS was 5.38 MPa. Biocompatibility properties of the constructs were tested by mitochondrial dehydrogenase activity, and in vitro studies showed that the PCL/3wt.%PVP/1wt.%HA composite construct had more cell viability than the other constructs by making use of the mesenchymal stem cell line.
Keywords: cartilage tissue engineering; mesenchymal stem cell; polycaprolactone; polyvinylpyrrolidone; CARTILAGE REPAIR; HYALURONIC-ACID; SCAFFOLDS; CHITOSAN; BONE; DEGRADATION; Orthopedics